Adsorbents derived from nitric acid-oxidised coal and activated with potassium hydroxide - Kucherenko, Volodymyr; Tamarkina, Yuliia; Redko, Anastasiia; Frolova, Iryna (Technologies and Engineering, 2025)
Alkaline activation is the most effective method for producing carbon-based adsorbents with a highly developed surface area (≥1,000 m2/g). However, its major drawback – the requirement for large quantities of alkali – necessitates research aimed at improving the process. This study aimed to quantitatively assess the effect of nitric acid oxidation of long-flame coal on the porous structure and adsorption properties of adsorbents produced by alkaline activation at a low KOH-to-coal ratio (≤1 g/g). Experimental, analytical and comparative scientific methods were employed. The properties of the adsorbents were characterised using infrared spectroscopy, porometry, and the kinetics and isotherms of 4-chlorophenol, methylene blue dye, and lead cation adsorption from aqueous solutions (at 25°C). It was found that pre-oxidation of the coal with nitric acid introduces ether, ester, phenolic, carboxylic, and nitro groups into the carbon matrix, resulting in a mass increase of up to 16% and significantly influencing the formation of the adsorbents. Increasing the HNO3-to-carbon ratio from 0 to 1.0 mol/mol reduces the adsorbent yield (from 50.2% to 33.85%), increases the specific surface area (from 1,685 m2/g to 2,216 m2/g), and improves adsorption properties by 25%-51%. The dominant portion (~80%) of the effect occurs within the range of ≤0.4 mol/mol. A comparison of the porous structure characteristics of the adsorbents revealed that oxidation primarily promotes the formation of subnanopores and mesopores with diameters of 2-5 nm. A comparison of adsorption properties showed that adsorbents derived from oxidised coal adsorb greater quantities of adsorbates (by a factor of 1.20-1.43) and with a higher initial rate (by a factor of 1.2-4.0). This property is particularly important for the rapid removal of highly toxic compounds from water. The adsorbent produced from oxidised coal possesses a more developed surface and a subnanoporous structure, and it exhibits greater adsorption activity than the material derived from non-oxidised coal. Pre-oxidation significantly enhances the adsorption capacity of activated carbon in capturing ecotoxicants from aqueous environments